Research Title: Strategic Orientation Reflections on Organizational Performance (Applied research in the Ministry of Defense / Inspector General) - سعد, علي موات; ناصر, محمد جاسم (Journal of Economics and Administrative Sciences, 2019)
The aim of the study was to study the implications of the strategic direction on organizational performance. The research was carried out in the Iraqi Ministry of Defense / Inspector General's Office for the purpose of identifying the nature of the relationship and the impact between the two variables. A sample of 60 people managers, department managers and directorates was targeted.The researcher tried to test hypotheses in the first chapter, which was devoted to the methodology of research and previous studies and found the following: (1) validity of the first hypothesis of the existence of a relationship of positive significance of the strategic direction in its sub-dimensions with organizational performance in the Office of Inspector General / Ministry of Defense. (2) the validity of the second hypothesis regarding the existence of a significant impact of the strategic orientation of its four dimensions in the organizational performance in the Office of Inspector General / Ministry of Defense. The second chapter of the research presented the strategic orientation in terms of concept, importance, and presentation dimensions. In addition to reviewing the organizational performance in detail. The third chapter presents the practical aspect of discussing the results and verifying the validity of the hypotheses in this research by analyzing the data of the study collected through the questionnaire prepared for this purpose through two subjects. The second section presents an analysis of the relationship between strategic orientation and organizational performance in the Office of the Inspector General / Ministry of Defense. Finally came the fourth chapter to present the most important conclusions and recommendations, and the research reached a set of results, the most important of which: - • The Department of the Inspector-General of the Iraqi Ministry of Defense adopts a clear vision and all administrative levels in accordance with the interests of the main beneficiaries and this is reflected in the level of performance of this organization.2 - The goals are realistic and applicable because they are clear to all, which helps the workers to achieve and thus demonstrated the effectiveness of the performance of the organization.3 - the need to adopt transparency and expand the circle of involvement of decision-makers without weakening the confidential nature of the supervisory work of the organization, which reflected positively on the level of performance.